An Online Child Adoption Application System - Ninie Azniera Binti Mohd,; Robiah Binti Hamzah, (Journal of Computing Technologies and Creative Content, 2023)
The Child Adoption Application System developed for the OrphanCare Foundation serves the purpose of facilitating the management of adoption applications. This web-based technology platform enables individuals to submit their adoption applications and streamlines the online application process. Users are required to register to access the system, and its objectives encompass researching and analyzing the system's requirements, incorporating stakeholder feedback, and designing an application system that caters to both users and administrators. The system leverages software tools such as Visual Studio Code, XAMPP, phpMyAdmin, Bootstrap, MySQL, and others. It also provides functionality for users to apply for the adoption process through the OrphanCare Foundation. Rigorous testing, including system and user acceptance testing, ensures the system's effectiveness. It can verify user eligibility based on specific criteria and maintains comprehensive records of children's information. Additionally, qualified users can access and submit adoption applications conveniently via the website.